Battlefield trauma care. (September 2018) - Berggren, Peter; Svensson, Filip; Lampi, Maria; Prytz, Erik
Introduction: Rapid and structured medical care is important to increase wounded patients' chances of survival in modern warfare. This requires a functioning medical chain.Aim: The aim of this study was to expand the knowledge of how the battlefield trauma care affects patient outcome in situations with a large number of casualties in the Swedish armed forces.Methods: An empirical study with a convergent parallel mixed methods design, which included observations and semi-structured interviews.Results: The results show that the trauma care performed at Role 1-units functioned well. The most prominent issue discovered was deficiency in transportation resources for medical evacuation throughout the entire medical chain.Conclusion: Despite that the trauma care performed at Role 1-units functions well, casualties are at risk for preventable complications or death. Improved transportation logistics are required to improve the medical capabilities of the Swedish armed forces.